The CSF IL-10 concentration is an effective diagnostic marker in immunocompetent primary CNS lymphoma and a potential prognostic biomarker in treatment-responsive patients. (July 2016) - Nguyen-Them, Ludovic; Costopoulos, Myrto; Tanguy, Marie-Laure; Houillier, Caroline; Choquet, Sylvain; Benanni, Hind; Elias-Shamieh, Rwaida; Armand, Marine; Faivre, Geraldine; Glaisner, Sylvie; Malak, Sandra; Vargaftig, Jacques; et al.
Abstract: Introduction: We aimed to confirm the diagnostic value and to evaluate the pre- and post-therapeutic prognostic value of cerebrospinal fluid (CSF) concentrations of interleukin (IL)-10 and IL-6 in patients with diffuse large B-cell primary central nervous system lymphoma (PCNSL). Patients and methods: IL-10 and IL-6 concentrations were measured in 79 patients with PCNSL at diagnosis and in 40 control individuals. Fifty-four PCNSL patients underwent repeat assessments starting at diagnosis. Results: The IL-10 concentration distinguished PCNSL from other neurologic diseases with a sensitivity of 88.6% and a specificity of 88.9% with a cutoff of 4 pg/ml. In a multivariate analysis of PCNSL patients, CSF involvement was associated with a higher IL-10 concentration (mean log (IL-10) of 4.4 versus 2.5 pg/ml, respectively, p = 0.0004). The pre-therapeutic IL-10 concentration had no prognostic impact on outcome. The IL-10 concentration decreased after treatment for most patients tested. Among patients with complete remission or partial remission, as evaluated by magnetic resonance imaging (MRI), a persistent detectable IL-10 level in the CSF at the end of treatment was associated with a negative impact on progression-free survival (PFS) (1-year PFS: 15%, 95% confidence interval [CI]: 2.5–38% versus 59%, 95% CI: 32–78%, respectively, p = 0.0004). Conclusion: Our study confirmed that IL-10 is a useful biomarker for the diagnosis of PCNSL. We highlight new findings showing that the IL-10 level in the CSF could be used as a surrogate marker for CSF involvement and that the post-treatment IL-10 concentration could complement standard MRI for therapeutic response assessment in PCNSL. Highlights: Interleukin-10 (IL-10) concentration in the cerebrospinal fluid is sensitive and specific for the diagnosis of primary central nervous system lymphoma. Higher IL-10 concentration is observed in patients with CSF involvement by lymphoma cells. Detectable IL-10 in CSF at the end of treatment is associated with a shorter progression-free survival.